Crossing and shooting patterns in the 1986 and 1998 World Cups for soccer - Pettit, A.; Hughes, M. (5th World Congress of Performance Analysis of Sport, 2001)
The purpose of this study was to provide an objective and quantitative analysis of crossing and shooting in elite soccer from the 1998 World Cup, and compare the results with the 1986 World Cup to examine how tactics and styles of play have changed in this period.